Evaluating Sequential Response Learning in the Rodent Operant Touchscreen System. Issue 10 (22nd October 2021) - Janickova, Helena; Kljakic, Ornela; Robbins, Trevor W.; Saksida, Lisa M.; Bussey, Timothy J.; Prado, Vania F.; Prado, Marco A. M.
Abstract: Sequential and cue‐directed response learning in rodents have been previously shown to depend on intact striatal signaling. In particular, these behaviors rely on striatal dopamine and acetylcholine release, with an impairment of sequential response learning evident in animal models with alterations in the two systems. Here we provide a protocol for testing sequential response/response chain learning using the rodent touchscreen system. Specifically, the present protocol is designed to implement the heterogeneous sequence task, adapted from Keeler et al. (2014), in the rodent touchscreen apparatus. This task has been used previously to assess complex motor learning and response selection in mice. In the following protocol, the task is performed in touchscreen‐based automated chambers with five response locations using food reinforcers to maintain performance. The sequence task requires the subject to make five nose pokes to white square stimuli appearing in five different locations sequentially from left to right. © 2021 Wiley Periodicals LLC. Basic Protocol : Implementation of the heterogeneous sequence task Support Protocol : Creation of the heterogeneous sequence task ABET II touchscreen schedule